2018
DOI: 10.1063/1.5018297
|View full text |Cite
|
Sign up to set email alerts
|

Collective orientational dynamics of pinned chemically-propelled nanorotors

Abstract: Collections of chemically propelled nanomotors free to move in solution can form dynamic clusters with diverse properties as a result of interactions through hydrodynamic flow and concentration fields, as well as direct intermolecular interactions between motors. Here, we study the collective rotational behavior of pinned sphere-dimer motors where direct motor-motor interactions play no role. Since the centers of mass of the motors are pinned, they cannot execute directed translational motion, but they can pum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Furthermore, assuming that the hydrodynamics are of a much shorter range than phoretic interactions [17], modeling the activity of the active particles as a constant velocity and creating a chemical sink field around the particles was shown [18]. Separate overdamped Langevin equations for active and passive tracers yield the positon of the passives, and besides emerging dynamics (gas-like, oscillating, and collapsing), the model captures well the decreasing speed of growing clusters observed experimentally [18].…”
Section: Spotlight On Theoretical Considerationsmentioning
confidence: 66%
“…Furthermore, assuming that the hydrodynamics are of a much shorter range than phoretic interactions [17], modeling the activity of the active particles as a constant velocity and creating a chemical sink field around the particles was shown [18]. Separate overdamped Langevin equations for active and passive tracers yield the positon of the passives, and besides emerging dynamics (gas-like, oscillating, and collapsing), the model captures well the decreasing speed of growing clusters observed experimentally [18].…”
Section: Spotlight On Theoretical Considerationsmentioning
confidence: 66%
“…The results provided in this paper should prove useful for such applications involving chemicallypowered diffusiophoretic motors. The concepts discussed here for active motor rotation are not restricted to spherical shapes and diffusiophoresis but are applicable to other geometries, such as sphere-dimer motors and other phoretic mechanisms, although detailed aspects of the description will require modification [21,27,32,54,55]. work was supported by Brain Pool Program through the National Research Foundation of Korea (NRF) funded by the Ministry of Science and ICT (grant number: NRF-2019H1D3A2A02102052) and supported in part by the Natural Sciences and Engineering Research Council of Canada and Compute Canada.…”
Section: Discussionmentioning
confidence: 99%
“…The MPCD method in turn has been used e.g. to explore hydrodynamic interactions in squirmers [234,235,298,299] and has also been generalized to account also for the chemical reaction dynamics at the surface of active colloids and to study the combined effects of phoretic and hydrodynamic interactions in self-diffusiophoretic colloids [260,300] as well as chemically powered nanomotors [262] and surface attached nanorotors [274]. Another simulation method which is frequently used to study the interactions between (spherical) active particles is the Stokesian dynamics method [301].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…For active Janus colloids pinned on a substrate, ref. [274] has shown that the combined effect of hydrodynamic and phoretic interactions can lead to states with highly correlated particle orientations. Also in this work the phoretic interactions have been found to play the dominant role for the observed collective behavior.…”
Section: Cross-interactionsmentioning
confidence: 99%